Model Dampak dan Keberlanjutan Pariwisata di Pulau Merah Kabupaten Banyuwangi - Yustita, Aprilia Divi; Hardiyanti, Siska Aprilia; Purwaningtyas, Ayu (Jurnal Master Pariwisata (JUMPA), 2020)
Banyuwangi is a region that actives in developing the tourism sectors because Banyuwangi has great potential of natural resources. The efforts of Banyuwangi local government implicate to the tourist amount visiting the tourism destination in Banyuwangi. Pulau Merah is one of the favorite destinations in Banyuwangi with high visitation rate. As the effect of various tourism activity in the region, the surrounding environment of tourism destination will gain the effect of tourism activity. The effects of tourism activity are such as bringing the economics values from economical aspect, socio culture, and environment. The best management of tourism object is always based on the achievement of sustainable tourism. This research discusses the effect and sustainable tourism model in Red Island. The used statistics analysis technique here is Structural Equation Model (SEM) by using AMOS software. The result of this research shows that the model fulfills the qualification of SEM assumption and qualifies the criteria of eligibility model. Keywords: Tourism Effect, Sustainable Tourism, Structural Equation Model